Implementation of Basic Obstetric and Neonatal Emergency Service Program (PONED) at Health Centers, Tegal - Rejeki, Sri Tanjung; Akhyar, Muhammad; R, Supriyadi Hari (Journal of Maternal and Child Health, 2016)
Background: Maternal mortality reached 33 cases in Tegal in 2015. Some measures had been taken to reduce maternal mortality rate and infant mortality rate, among others was basic obstetric and neonatal emergency service program (PONED). The PONED program was operated by health centers with inpatients services 24 hours a day and 7 days a week. This study evaluated the Implementation of Basic Obstetric and Neonatal Emergency Service Program (PONED) at Health Centers, Tegal. Subjects and Method: This was an evaluation study with qualitative approach and CIPP (context, input, process, product) framework. This study was conducted in Tegal, Central Java. A total of 10 key informants, including Head of Family Health and Nutrition Division at the District Health Office Tegal, Head of Health Centers, Midwife responsible for operating PONED, mothers with post heavy pre-eclampsia, were selected for this study. The data were collected by in-depth interview, observation, and document review.